Highly Relativistic Electron Flux Enhancement During the Weak Geomagnetic Storm of April–May 2017. Issue 6 (27th June 2019) - Katsavrias, Ch.; Sandberg, I.; Li, W.; Podladchikova, O.; Daglis, I.A.; Papadimitriou, C.; Tsironis, C.; Aminalragia‐Giamini, S.
Abstract: We report observations of energetic electron flux and phase space density to show that a relatively weak magnetic storm with Sym‐H min ≈−50 nT, resulted in a relativistic and ultrarelativistic electron enhancement of two orders of magnitude similar to the St. Patrick's event of 2015, an extreme storm with Sym‐H min ≈−235 nT. This enhancement appeared at energies up to ≈10 MeV, lasted for at least 24 days, and was not recorded in geosynchronous orbit where most space weather alert data are collected. By combined analysis of phase space density radial profiles and Fokker‐Planck simulation, we show that the enhancement of relativistic and ultrarelativistic electrons is caused by different mechanisms: first, chorus waves during the intense substorm injections of 21–25 April accelerate the seed electron population to relativistic energies and redistribute them while inward diffusion driven by Pc5 Ultra‐Low Frequency (ULF) waves further accelerates them to ultrarelativistic energies. Key Points: Long‐lasting multi‐MeV electron enhancement during a period of a relatively weak geomagnetic storm was not recorded in GEO Electron seed population was accelerated to relativistic energies by the enhanced chorus waves Relativistic electrons were further accelerated up to 10 MeV by inward diffusion